Description of the Increase in Hemoglobin Levels in Pregnant Women with Anemia at PKU Muhammadiyah Gombong Hospital: Gambaran Peningkatan Kadar Hemoglobin pada Ibu Hamil dengan Anemia di RS PKU Muhammadiyah Gombong - Puspita, Lea Cindy; Riyanti, Eka (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Background: One of the indirect causes of maternal mortality is anemia in pregnancy. Anemia is a condition where hemoglobin levels are less than they should be. Iron is an important element in the formation of hemoglobin. Fe tablets are very influential to increase hemoglobin. Objective: To know the picture of increasing hemoglobin levels in pregnant women with anemia at PKU Muhammadiyah Gombong Hospital. Methods: This study is a quantitative study with a cross sectional approach. The collection technique used sampling. Samples taken were 80 respondents, with purposive sampling technique. Data analysis using excel. Results: Hemoglobin levels of pregnant women with anemia at PKU Muhammadiyah Gombong Hospital increased after taking Fe tablets with an average increase of 0.96. A total of 66 respondents experienced an increase with a percentage of 82.5% and a total of 14 respondents experienced a decrease with a percentage of 17.5% due to the side effects of nausea and vomiting. Conclusion: Pregnant women with anemia at PKU Muhammadiyah Gombong Hospital who regularly consume Fe tablets have increased hemoglobin levels. Recommendations: future researchers are expected to examine other foods/drinks that can increase hemoglobin levels.